ANALISIS KESULITAN GURU IPA DALAM PEMBELAJARAN IPA DI SMP DAN SD - Prayunisa, Fena; Marzuki, Ahmad Dedi (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to analyze the difficulties experienced by science teachers in learning science in junior high schools and elementary schools, to explain the obstacles experienced by teachers in learning science, and to explain the factors that cause difficulties in learning science in junior high schools and elementary schools. The type of research used is qualitative research with descriptive methods. The sample in this study were all science educators at MI NW Kumbung and MTs NW Kumbung. Sampling was done by total sampling technique. The research data is in the form of data on constraints in the implementation of Integrated Science learning obtained from closed questionnaires and semi-open questionnaires from educator responses which are analyzed using descriptive qualitative and information obtained from interviews. The results show that the preparation of lesson plans for MI NW Kumbung and MTs NW Kumbung has a percentage of 70%. Presentation of Materials at MI NW Kumbung and Mts NW Kumbung obtained a percentage of 60% & 65% which is still low. IPA graduate teachers that teach science subjects at MI is a factor that cause teachers' difficulties in teaching science extrinsically are the lack of laboratory facilities and the lack of training activities and KKG and the lack of support from schools.